THE INFLUENCE OF FIRM SIZE, ENVIRONMENTAL PERFORMANCE, BOARD INDEPENDENCE, AND BOARD GENDER DIVERSITY ON CARBON EMISSION DISCLOSURE IN ENERGY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (2023–2024) - Risanty; Adi Syah Putra; Juwita Agustrisna; Yesica Exaudy Napitu (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to determine the influence of firm size, environmental performance, board independence, and board gender diversity on carbon emission disclosure among energy companies listed on the Indonesia Stock Exchange during the 2023–2024 period. The study utilized a sample of 61 companies selected through purposive sampling. Data analysis was conducted using multiple linear regression. The results indicate that firm size and environmental performance have a positive effect, whereas board independence and board gender diversity have no effect.